Ontological model for evaluating the effectiveness of scientific institutions - Globа, Larisa S.; Novogrudskaya, Rina L.; Zadoienko, Bohdan O. (Bulletin of V.N. Karazin Kharkiv National University, series «Mathematical modeling. Information technology. Automated control systems», 2020)
The article presents an approach to assessing the quality of functioning of scientific institutions based on ontologies. Today, there are a large number of scientific institutions and specialized organizations whose efficiency depends on the quality of the services they provide. In the course of their operation, institutions accumulate a large amount of information (scientific articles, reports, employee ratings, economic indicators, etc.) that can be used to evaluate them automatically by national criteria. This study proposes to use an ontological model to store, present and manipulate with such information. Ontologies are new intelligent tools for finding resources on the Internet, new methods for representing and processing knowledge and queries. They are able to accurately and efficiently describe the semantics of data for a certain domain and solve the problem of incompatibility and inconsistency of concepts. The ontological approach allows the continuous improvement of the model based on basic ontologies by completing and developing them The ontology will allow not only to structure and systematize the data of scientific institutions, but also to perform the procedure of quality assessment through the mechanism of ontological logical inference. A general ontology for describing the activities of scientific institutions is represented by a system of five connected components. In the paper the structure of such a system is described, basic elements of its ontologies and the connections between them are highlighted. The ontology of the scientific institution activity is developed using specific technological platform TEDAOS - “Transdisciplinary Educational Dialogues of Applications’ Ontology Systems”.